Anaerobically digested blackwater treatment by simultaneous denitrification and anammox processes: Feeding loading affects reactor performance and microbial community succession. (February 2020) - Zhou, Yun; Guo, Bing; Zhang, Lei; Zou, Xin; Yang, Sen; Zhang, Huixin; Xia, Siqing; Liu, Yang
Abstract: Source diverted blackwater collected from toilets can be anaerobically digested to recover energy. The anaerobically digested blackwater (ADB) contains high levels of ammonium and low carbon to nitrogen (C/N) ratio. In the present study, ADB was treated by a two-stage nitritation-denitrification/anammox process in an integrated fixed film activated sludge-continuous flow reactor (IFAS-CFR). NH4 + -N, NO2 - -N, total nitrogen (TN), and chemical oxygen demand (COD) removal efficiencies were 80%, 82%, 76%, and 78%, respectively. Anaerobic ammonium oxidation (anammox) and denitrification contributed to 44–48%, and 52–56% of total nitrogen removal, respectively. Both of the protein- and humic acid-like matters were removed during the process. An increase in feed load promoted the sustained growth of anammox bacteria— Candidatus Brocadia in the biofilm, as well as an increase of denitrifiers ( Pseudomonas, Thermotonus, Phodanobacter, Caulobacter ) in both biofilm and suspended biomass, which remained higher in the suspended biomass than in biofilm. Overall, biofilm had higher nitrogen removal efficiency than suspended biomass, while suspended biomass had a higher COD removal efficiency than biofilm. Graphical abstract: Image 1 Highlights: Denitrification-Anammox process showed a stable nitrogen and COD removal performance. Anammox and denitrification separately contributed to 44–48% and 52–56% of TN removal. Proteins were biodegraded preferentially to humic acid-like matters at high feeding loadings. Increasing feed load promoted the growth of anammox bacteria and denitrifiers in biofilm. Biofilm had higher nitrogen removal rate than suspended sludge, but opposite for COD removal.